Treatment Adherence And Its Impact On Glycemic Control In Patients With Diabetes Mellitus Type 2 In Working Area Of Klatak Health Center Banyuwangi 2024 - Andrik Hermanto; Masroni Masroni; Dedek Nabila Syakif (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: One of the factors that can affect treatment adherence in patients with type 2 diabetes mellitus is glycemic results, if glycemic control is poor then the implementation of treatment compliance can be a motivation for glycemic control. Purpose: This study aims to determine the relationship between treatment adherence and its impact on glycemic control in patients with type 2 diabetes mellitus in the Klatak Health Center working area in 2024. Methods: This study used a cross sectional design with purposive sampling and a sample size of 35 respondents. Data collection using the MTAQDM questionnaire (modified treatment adherence questionnaire in DM patients) and observation sheets and then analyzed using the spearmen rank test. Results: All patients (100%) were in the adherence category following treatment adherence activities and almost all patients (97%) were in the diabetic category. Based on the results of the analysis obtained a P-value of 0.628 (p>0.05) which means that there is no relationship between treatment adherence and the impact of glycemic control, with a correlation of 0.085 which shows a correlation with very weak strength. Conclusion: Respondents who adhere to treatment adherence do not affect their glycemic control and adhere to treatment but HbA1c is not controlled, because many factors can affect it.